2019
DOI: 10.3390/soilsystems3040064
|View full text |Cite
|
Sign up to set email alerts
|

Control of Soil Extracellular Enzyme Activities by Clay Minerals—Perspectives on Microbial Responses

Abstract: Knowledge of how interactions of clay minerals and extracellular enzymes (EEs) influence organic matter turnover in soils are still under discussion. We studied the effect of different montmorillonite contents on EE activities, using two experiments—(1) an adsorption experiment with a commercially available enzyme (α-glucosidase) and (2) an incubation experiment (10 days) where microorganisms were stimulated to produce enzymes through organic carbon (OC) addition (starch and cellulose). Soil mixtures with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 56 publications
1
17
1
Order By: Relevance
“…Nonetheless, we found the specific activities of the adsorbed enzymes to be higher than those of the free enzymes immediately after adsorption ( Figure 2 ) and throughout the entire study period ( Figure S3 ). This is in contrast to common findings of reduced activities upon enzyme adsorption to minerals [ 9 , 10 , 39 ], although most studies report potential rather than specific enzyme activities. Nevertheless, our observation aligns with the result of Giaveno et al [ 40 ], who reported a 20% increase in potential phytase activity upon adsorption to hematite.…”
Section: Discussioncontrasting
confidence: 94%
See 4 more Smart Citations
“…Nonetheless, we found the specific activities of the adsorbed enzymes to be higher than those of the free enzymes immediately after adsorption ( Figure 2 ) and throughout the entire study period ( Figure S3 ). This is in contrast to common findings of reduced activities upon enzyme adsorption to minerals [ 9 , 10 , 39 ], although most studies report potential rather than specific enzyme activities. Nevertheless, our observation aligns with the result of Giaveno et al [ 40 ], who reported a 20% increase in potential phytase activity upon adsorption to hematite.…”
Section: Discussioncontrasting
confidence: 94%
“…However, we did not find a universal relationship between the availability of adsorption sites, the adsorption of enzymes, their specific activity, and persistence, which is applicable for different types of minerals. Nevertheless, the presumed reduction in enzyme activities due to adsorption in soils [ 9 , 10 , 38 ] may not always hold true, as the effect on each enzyme likely varies with mineral types, as well as enzymes and the respective sorption-site density provided on the mineral surfaces. Additionally, soil minerals may regulate persistence of extracellular enzymes in soil by, e.g., protection from proteolytic enzymes and direct microbial attack; however, such evidence has mostly been tested over short periods, such as 24 h [ 17 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations